DEFINICIÓN, CRONOLOGÍA Y TIPOLOGÍA DEL RETABLO SEVILLANO DEL RENACIMIENTO - Palomero Paramo, Jesús M. (Imafronte, 1989)
This paper starts from a terminological definition, based upon the Spanish lexical repertories since the end of the XVth century up to the end of the XVIIIth century, to continue with an approach to the reason and operation of the reredos inside the temple. Then, a chronology of the Sevillian retable is established, separaring three different periods: plareresque (1540-I580), romanistic (1581 -1600) and purist (1601-1629). It follows a study of the more significant works and artists in each of the three periods, an analysis of typologies, paving attention to the location inside the temple (major or collateral), plan (linear, eight-sided) and purpose (sacramental, communion rail, reliquary, sepulcher). We also offer a classification, following the iconographic repertory, in rosary- and apocalypticul- retables. Finally, attending to the architectural structure, we classi' them into triptych -, tabernacle -, crucifix-, stage -, frontand illusionist- retables. They all are illustrated with numerous examples, both existing and taken from printed repertories, joined to biographical sketches of the masters who made them.